Mapping Mexican COVID-19 vulnerability at municipal scale - Rainer Ressl; Carmen Luz Martínez; Miriam Elizabeth Piña Camacho; Florian Hruby; José Manuel Dávila Rosas; Manuel Ernesto Rodríguez Huesca; Raúl Jimenez-Rosenberg (Terra Digitalis)
This paper presents an interactive map related to the population vulnerability concerning COVID-19 at the municipal level for Mexico. A vulnerability index was modeled using seven socioeconomic/sociodemographic variables and one health-care related variable, all with relevance to a health contingency such as COVID-19. The resulting indicator expresses the municipal vulnerability to face a sanitary crisis such as COVID-19 in five categories. Data for each of the eight variables were first categorized in quintiles. A pairwise comparison matrix was used to weight these variables in relation to their estimated relevance for the municipal vulnerability. With respect to COVID-19 vulnerability, Mexican municipalities show the following results: 1.6% (very low), 18.7% (low), 46.6% (medium), 24.6% (high), 8.5% (very high).